A HST1‐like gene controls tiller angle through regulating endogenous auxin in common wheat. Issue 1 (14th October 2022) - Zhao, Lei; Zheng, Yueting; Wang, Ying; Wang, Shasha; Wang, Tongzhu; Wang, Canguan; Chen, Yue; Zhang, Kunpu; Zhang, Ning; Dong, Zhongdong; Chen, Feng
Summary: Tiller angle is one of the most important agronomic traits and one key factor for wheat ideal plant architecture, which can both increase photosynthetic efficiency and greatly enhance grain yield. Here, a deacetylase HST1‐like ( TaHST1L ) gene controlling wheat tiller angle was identified by the combination of a genome‐wide association study (GWAS) and bulked segregant analysis (BSA). Ethyl methane sulfonate (EMS)‐mutagenized tetraploid wheat lines with the premature stop codon of TaHST1L exhibited significantly smaller tiller angles than the wild type. TaHST1L‐ overexpressing (OE) plants exhibited significantly larger tiller angles and increased tiller numbers in both winter and spring wheat, while TaHST1L‐ silenced RNAi plants displayed significantly smaller tiller angles and decreased tiller numbers. Moreover, TaHST1L strongly interacted with TaIAA17 and inhibited its expression at the protein level, and thus possibly improved the content of endogenous auxin in the basal tissue of tillers. The transcriptomics and metabolomics results indicated that TaHST1L might change plant architecture by mediating auxin signal transduction and regulating endogenous auxin levels. In addition, a 242‐bp insertion/deletion (InDel) in the TaHST1L‐A1 promoter altered transcriptional activity and TaHST1L‐A1b allele with the 242‐bp insertion widened the tiller angle of TaHST1L‐ OE transgenic rice plants. Wheat varieties with TaHST1L‐A1b allele possessed the increased tiller angle and grain yield. Further analysis in wheat and its progenitors indicated that the 242‐bp InDel possibly originated from wild emmer and was strongly domesticated in the current varieties. Therefore, TaHST1L involved in the auxin signalling pathway showed the big potential to improve wheat yield by controlling plant architecture. Abstract : TaHST1L interacting with TaIAA17 controls wheat tiller angle to affect grain yield through regulating endogenous auxin.